CRENÇAS E ATITUDES DE UMA PROFESSORA DE ESPANHOL DE UMA ESCOLA PÚBLICA DO INTERIOR DO PARANÁ E AS POLÍTICAS LINGUÍSTICAS - Braga, Lucimar Araujo (2013)
Reflecting the possibility of talking about beliefs involving teacher´s behavior in class instigated us to try to understand how these attitudes appear in language classrooms. Barcelos (2004, 2006, 2010, 2011), considers that beliefs have great power upon our behavior and actions, existing an inter-relation among beliefs, attitudes and identity construction. Understanding teacher´s identity as an ongoing process (TADEU DA SILVA,2004) that shapes itself to the reality inside the classroom and knowing that beliefs and attitudes can be modified, as well as language policies are inter-related in this process all the time this research, with a qualitative nature, aims at observing,identifying and analyzing beliefs and attitudes of a teacher from a public school located in Paraná. Our studies comprehended Spanish teaching/learning process, as a case study. Based on Picanço (2003), we gathered historical facts related to language teaching/learning process analyzed through the language policy in Brazil, specifically in Paraná. In the theoretical revision, we present some positions about studies related to beliefs and attitudes according to Le Bon (2002); Barcelos (2004, 2006, 2010, 2011);Vieira-Abrahão (2004, 2010, 2011) e Silva (2010, 2011) among others. Some questions guided this work: “ which beliefs the teacher shows in her practice?” “Are there any difference between teacher´s beliefs and acts and the language policy concerned to language teaching?” “What relations do these beliefs establish with the teacher´s actions?”. In general terms, the beliefs presented in Spanish language classes are similar to some beliefs that have already appeared in other research works, once the participant showed beliefs with these thematic: a) beliefs about the learning process of FL by FL;b) Beliefs about how to deal with an error; c) Beliefs about the lack of interest in learning FL; d) Beliefs about the importance of learning S/FL; e) Beliefs about student´s autonomy in learning language; f) Beliefs about the role of the vocabulary in S/FL classes; g) Beliefs about the ludic role in the S/FL classes; h) Beliefs about the necessity of persuade students to learn; i) Beliefs about the “facility” in learning S/FL; and j) Beliefs about the group work activities role in class.